IBM system storage DS6000 series copy services with IBM system Z - Castets, Gustavo; Dufrasne, Bertrand; Baird, Stephen; Bauer, Werner; Brown, Denise; Jamsek, Jana; Kalabza, Wenzel; Oscheka, Markus; Thia, Ying; Tondini, Robert (IBM Corporation, 2006)
This IBM Redbooks publication will help you plan, install, and configure the IBM System Storage DS6000 Copy Services functions in System z environments, and provides the details you need to implement and manage these functions. The book includes hints and tips. This document is intended to help you either to design and set up a new Copy Services installation, or to migrate from an existing installation. It also addresses functionality and terminology differences from other IBM Copy Services products. You can read this book in conjunction with the book IBM System Storage DS6000 Series: Architecture and Implementation, SG24-6781 . You may also wish to refer to the companion book for the DS6000 that supports the configuration of the Copy Services functions in open systems environments, IBM System Storage DS6000 Series: Copy Services in Open Environments, SG24-6783.
Includes bibliographical references and index
Keywords: Storage area networks (Computer networks); Electronic data processing -- Backup processing alternatives; Data recovery (Computer science); Réseaux de stockage (Informatique); Sauvegarde (Informatique); Récupération des données (Informatique)